Implementation of the Dual Vocational Education and Training Program in Chile, 1992-2007 - Ascui, Juan [Verfasser]; Troncoso, Francisco [Verfasser] (My University, 2012)
"Chile's dual vocational education and training (VET) program models the German approach to training skilled trades workers. The two countries signed an agreement in 1991 whereby Chile adapted Germany's dual system to fit its institutional and cultural realities. Few articles examine the similarities and differences between the German dual system and Chile's program, and it appears that no other articles exist in the English language that examine the development of this program in Chile. To fill this gap, the following article outlines Germany's and Chile's school systems and provides overviews of their approaches to dual VET. The article describes how the dual program was implemented in Chile including the factors that drove the reforms, the challenges encountered in establishing the system and the key actions taken by those leading the change. In Chile, the dual approach to VET is more accurately referred to as the 'dual program' because it is a relatively small component of the country's broader education system and is run by the schools. The dual program comprises just 10 per cent of VET school students in Chile. Conversely, the dual system in Germany is more widespread and is led by business." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 2.3 Berufsbildungspolitik; I 2.3.3 Lateinamerika; Berufsbildungssystem; Duales System; Transfer; Bildungsreform; Chile